The future of urban clean water and sanitation - Jamwal, P.; Brown, R.; Kookana, R.; Drechsel, Pay; McDonald, R.; Vorosmarty, C.J.; Vliet, M.T.H. van; Bhaduri, Anik (Elsevier, 2019)
Billions of people currently lack clean water and sanitation. By 2050 the global population will have grown to nearly 10 billion, over two-thirds of whom will live in urban areas. This Voices asks: what are the research and water-management priorities to ensure clean water and sanitation in the world’s cities?